2014
DOI: 10.1039/c4sm01435a
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property relationships of symmetrical and asymmetrical azobenzene derivatives as gelators and their self-assemblies

Abstract: Two different series of symmetrical and asymmetrical azobenzenes containing terminal cholesteryl/adamantyl derivatives (SAC/SAA and AAC) with varying spacer lengths (alkyl chains) have been developed. The gelation and aggregation of these derivatives were studied relative to structural motifs, spacer lengths, solvent affinity, temperatures and light conditions. Among these derivatives, the cholesteryl derivatives that have short alkyl chains (<3) act as efficient gelators in a variety of solvents. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Considering the longer molecular structure here (0.9 nm) than Ad (0.60 nm) and FcM (0.70 nm) groups, the adjacent Azo groups might not be packed in the same plane like the two others. The π-π stacking of Azo groups could adopt a face-to-face packing, resulting in a small D value [17]. The structure directing role of AOT here was also certified by a control experiment.…”
Section: Morphology and Structure Of The Aggregatementioning
confidence: 95%
“…Considering the longer molecular structure here (0.9 nm) than Ad (0.60 nm) and FcM (0.70 nm) groups, the adjacent Azo groups might not be packed in the same plane like the two others. The π-π stacking of Azo groups could adopt a face-to-face packing, resulting in a small D value [17]. The structure directing role of AOT here was also certified by a control experiment.…”
Section: Morphology and Structure Of The Aggregatementioning
confidence: 95%
“…A densely packed fibrous morphology was observed for the xerogel of PyMC in xylene, where gelation occurred at room temperature, indicating a strong interaction between the solvent and a gelator molecule, which is reasonable since the intermolecular interactions are more extensive in non-polar solvents than in polar solvents. 13 Helical structures, however, could not be seen in xylene. The morphological behaviors of xerogels were investigated by SEM analysis, and the results were depicted in Fig.…”
Section: Morphological Studiesmentioning
confidence: 97%
“…The structures of the LMWGs have been regulated successfully by changing the components of L or A, and the resulting gelators are able to gel a range of solvents including protic/aprotic and polar/nonpolar solvents. 11,12 Very recently we reported 13 the aggregation behavior of azobenzenecholesteryl-based A(LS) 2 -type gelators with respect to varying spacer length [the linker (L) between the azobenzene (A) and the cholesteryl unit (S)], in which we found that the azobenzene derivatives with either no alkyl or a short alkyl chain acted as more efficient gelators compared to the long chain azobenzene derivatives. Moreover, in our previous reports, 14 clear helicity was seen through TEM only in the gelator not possessing an alkyl chain between the core (A) and the terminal cholesteryl unit (S).…”
Section: Introductionmentioning
confidence: 97%
“…† Interestingly, while complexes 5, 8 and 9 exhibit fibrous structures that are commonly seen in the literature, complex 7 exhibits unusual globular-shaped aggregates in the TEM images. 56 The lack of fibrous network may account for the lower stability of the gel, as reflected by the low sol-gel transition temperature as well as the long time required for gel formation, probably resulting from the relatively short single alkoxy chain. 5(c) and (d), respectively.…”
Section: Bond Lengths (å)mentioning
confidence: 99%
“…5(c)). 56 The lack of fibrous network may account for the lower stability of the gel, as reflected by the low sol-gel transition temperature as well as the long time required for gel formation, probably resulting from the relatively short single alkoxy chain. In contrast, complex 8, with a longer alkoxy chain, could exhibit a stronger hydrophobic-hydrophobic interaction, tends to form an extensive fibrous network and gives a higher sol-gel transition temperature.…”
Section: Gelation Studiesmentioning
confidence: 99%